(untitled) (Revista Inclusiones, 2020)
The main objective of this paper is to specify and develop the scientific foundations of the operation of infrastructure in the Russian fishery complex by means of analysis of the external and internal factors influencing the production, distribution and consumption of fish and seafood. The state of production and consumption of fish and seafood in Russia is determined subject to the development of infrastructure. Current trends of the world fish and seafood markets are analysed. A brief assessment is given to state support measures in the Russian fishery complex. Infrastructure and other factors influencing the development of the Russian fishery complex are identified. Main directions are formulated for state policies in advancing the development of the Russian fishery complex by way of enhancement of major infrastructure components.